(untitled) (Journal of the College of Basic Education, 2023)
The present study was conduction to have a clearer integrative idea on the impact of immunological abnormalities including a set of auto antibodies on the clinical expression of lupus among Iraqi Arab patients, compared with a normal population matched in ethnic background. A total of (39) well diagnosed patients with lupus attending the rheumatology clinic of medical city in Baghdad (from Jun – 2005 to October – 2006) have been studied compared with (40) normal individuals of a blood bank donors as a general control. Indirect immunofluorescent technique was used to assess the prevalence of antinuclear antibody among subjects group, while other auto antibodies including anti – ds DNA, anti – Sm, anti – Ro, anti – La, anti – Sm RNP, and anti- cardiolipin antibodies were detected with enzyme immuno assay (EIA) and rheumatoid factor with latex agglutination. Patient’s group reported prevalence of all the eight sero immunological abnormalities in a statistically significant way, compared to general control. The risk for having a positive immunological marker for cases (represented by odds ratio) ranged between (7.5) for rheumatoid factor to (61.2) for antinuclear antibodies. Besides, selected auto antibodies were significantly associated with particular manifestation. Patients testing positive for rheumatoid factor had a significant risk of having malar rush (OR = 11.0 , P < 0.05) and those how had positive results for anti – ds DNA and anti – Sm antibodies had a significant risk of having renal involvement (OR = 4.7 and 4.3 respectively , P < 0.05) , while having anti – Ro antibodies decrease the risk of developing arthropathy (OR=0.2, P < 0.05). Nonetheless,